Geopolymerization: a promising technique for membrane synthesis. (23rd November 2021) - Sadiq, Muhammad; Naveed, Amir; Arif, Muhammad; Hassan, Saima; Afridi, Shaista; Asif, Muhammad; Sultana, Sabeeh; Amin, Noor-ul; Younas, Mohammad; Khan, Muhammad Naeem; Jiang, Heqing; Gul, Saeed
Abstract: Ceramic membranes are considered superior over their polymeric counterparts for applications at high temperature, pressure, and in aggressive environments with additional advantages of cleaning at high temperature. Preparation of porous ceramic membrane is expensive because the ceramic materials cannot be processed in a liquid state as polymers. Ceramic membrane synthesis involved solid powder preparation, consolidation, suspension formation, calcination, and sintering temperature which makes its synthesis very expensive. Geopolymerization is a heterogeneous reaction of aluminosilicate materials and chemical activators to form a three-dimensional structure having high mechanical strength without sintering. The overall percent energy and cost-saving of geopolymeric membranes were compared with conventional ceramic membranes. Recently, the geopolymerization technique has been used for membrane synthesis to replace conventional ceramic membrane synthesis. The objective of this review article is to discuss the potential opportunities and challenges in the synthesis and application of geopolymeric membranes.